Nano-Pulse Stimulation is a physical modality that can trigger immunogenic tumor cell death - Richard Nuccitelli; Amanda McDaniel; Snjezana Anand; John Cha; Zachary Mallon; Jon Casey Berridge; Darrin Uecker (Journal for ImmunoTherapy of Cancer, 2017)
Abstract Background We have been developing a non-thermal, drug-free tumor therapy called Nano-Pulse Stimulation (NPS) that delivers ultrashort electric pulses to tumor cells which eliminates the tumor and inhibits secondary tumor growth. We hypothesized that the mechanism for inhibiting secondary tumor growth involves stimulating an adaptive immune response via an immunogenic form of apoptosis, commonly known as immunogenic cell death (ICD). ICD is characterized by the emission of danger-associated molecular patterns (DAMPs) that serve to recruit immune cells to the site of the tumor. Here we present evidence that NPS stimulates both caspase 3/7 activation indicative of apoptosis, as well as the emission of three critical DAMPs: ecto-calreticulin (CRT), ATP and HMGB1. Methods After treating three separate cancer cell lines (MCA205, McA-RH7777, Jurkat E6-1) with NPS, cells were incubated at 37 °C. Cell-culture supernatants were collected after three-hours to measure for activated caspases 3/7 and after 24 h to measure CRT, ATP and HMGB1 levels. We measured the changes in caspase-3 activation with Caspase-Glo® by Promega, ecto-CRT with anti-CRT antibody and flow cytometry, ATP by luciferase light generation and HMGB1 by ELISA. Results The initiation of apoptosis in cultured cells is greatest at 15 kV/cm and requires 50 A/cm2. Reducing this current inhibits cell death. Activated caspase-3 increases 8-fold in Jurkat E6-1 cells and 40% in rat hepatocellular carcinoma and mouse fibrosarcoma cells by 3 h post treatment. This increase is non-linear and peaks at 15–20 J/mL for all field strengths. 10 and 30 kV/cm fields exhibited the lowest response and the 12 and 15 kV/cm fields stimulated the largest amount of caspase activation. We measured the three DAMPs 24 h after treatment. The expression of cell surface CRT increased in an energy-dependent manner in the NPS treated samples. Expression levels reached or exceeded the expression levels in the majority of the anthracycline-treated samples at energies between 25 and 50 J/mL. Similar to the caspase response at 3 h, secreted ATP peaked at 15 J/mL and then rapidly declined at 25 J/mL. HMGB1 release increased as treatment energy increased and reached levels comparable to the anthracycline-treated groups between 10 and 25 J/mL. Conclusion Nano-Pulse Stimulation treatment at specific energies was able to trigger the emission of three key DAMPs at levels comparable to Doxorubicin and Mitoxantrone, two known inducers of immunogenic cell death (ICD). Therefore NPS is a physical modality that can trigger immunogenic cell death in tumor cells.